Pemanfaatan Tepung Kedelai Sebagai Bahan SubstitusiSus Kering Tepung Mocaf Dengan Variasi Penambahan Jahe - Layla, Noor, Dr. Nanik Suhartatik, S.TP., M.P (2015)
Dry choux pastry is one of choux pastry that originated from a mixture of water, salt, margarine, flour, and eggs that have a crunchy texture. Dry choux pastry not only produced with standard materials from wheat flour, but can be produced from other types of flour such as mocaf flour and soybean flour. Mocaf flour is a cassava flour which is done by fermentation. Soybean flour containing not less than 50 % protein and be a very good source of isoflavon.. Ginger has a main component of essential oil that has a fragrant odor cause by zingiberen and zingiberol. The purpose of this study was to know the protein content and organoleptic quality of dry choux pastry with soybean flour and mocaf flour formulations with additional ginger variations. The study design using completely randomized design with 2 factors: factor 1 : soybean flour : mocaf flour rasio (0 : 100 (T0), 25:75 (T1) , 50:50 (T2), 75:25 (T3), 100 : 0 (T4) and factor 2 : extract of ginger (2 % ( J1 ) and 3 % ( J3 )) with 3 replications from each treatment. The results showed that the highest protein content in the dry choux pastry treatment was T4J2 (formulations 100 % soybean flour: 0 % mocaf flour and ginger extract 3 %) to reach 13.01% protein content. Treatment T2J2 (50 % formulations soybean flour: 50 % mocaf flour and ginger extract 3 %) had no unpleasant aroma, savory flavor, crunchy texture, and most preferred by consumers.